Validation of a Side‐Scan Sonar Method for Quantifying Walleye Spawning Habitat Availability in the Littoral Zone of Northern Wisconsin Lakes. (20th July 2016) - Richter, Jacob T.; Sloss, Brian L.; Isermann, Daniel A.
Abstract: Previous research has generally ignored the potential effects of spawning habitat availability and quality on recruitment of Walleye Sander vitreus, largely because information on spawning habitat is lacking for many lakes. Furthermore, traditional transect‐based methods used to describe habitat are time and labor intensive. Our objectives were to determine if side‐scan sonar could be used to accurately classify Walleye spawning habitat in the nearshore littoral zone and provide lakewide estimates of spawning habitat availability similar to estimates obtained from a transect–quadrat‐based method. Based on assessments completed on 16 northern Wisconsin lakes, interpretation of side‐scan sonar images resulted in correct identification of substrate size‐class for 93% (177 of 191) of selected locations and all incorrect classifications were within ± 1 class of the correct substrate size‐class. Gravel, cobble, and rubble substrates were incorrectly identified from side‐scan images in only two instances (1% misclassification), suggesting that side‐scan sonar can be used to accurately identify preferred Walleye spawning substrates. Additionally, we detected no significant differences in estimates of lakewide littoral zone substrate compositions estimated using side‐scan sonar and a traditional transect–quadrat‐based method. Our results indicate that side‐scan sonar offers a practical, accurate, and efficient technique for assessing substrate composition and quantifying potential Walleye spawning habitat in the nearshore littoral zone of north temperate lakes. Received December 1, 2015; accepted March 24, 2016 Published online July 20, 2016